1999
DOI: 10.1038/sj.hdy.6886200
|View full text |Cite
|
Sign up to set email alerts
|

Crosses between sexual and apomictic dandelions (Taraxacum). II. The breakdown of apomixis

Abstract: Some dandelions are diplosporous gametophytic apomicts. In order to study the inheritance and breakdown of apomixis, crosses were made between diploid sexuals and triploid apomicts. To investigate their breeding system, four nonapomictic diploid and 10 nonapomictic triploid hybrids were pollinated with diploids and the progenies were analysed. Seed fertility was signi®cantly reduced in two diploid hybrids. Nine triploid hybrids were fertile and could be classi®ed into three types, with respect to the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Asexual variants of the common dandelion, T. officinale , are polyploid (usually triploid, 3x = 24) obligate apomicts that produce clonal seeds in a process that involves unreduced egg cell formation (diplospory), parthenogenic embryo development and autonomous endosperm formation [40]. We used progeny from three apomictic genotypes: AS34, which was produced in an experimental cross between a sexual diploid mother and diploid pollen from a triploid father [41]; and A68 and H72, which are both natural apomicts that were previously collected from the field.…”
Section: Methodsmentioning
confidence: 99%
“…Asexual variants of the common dandelion, T. officinale , are polyploid (usually triploid, 3x = 24) obligate apomicts that produce clonal seeds in a process that involves unreduced egg cell formation (diplospory), parthenogenic embryo development and autonomous endosperm formation [40]. We used progeny from three apomictic genotypes: AS34, which was produced in an experimental cross between a sexual diploid mother and diploid pollen from a triploid father [41]; and A68 and H72, which are both natural apomicts that were previously collected from the field.…”
Section: Methodsmentioning
confidence: 99%
“…The genus Taraxacum contains a complex of diploid sexual and polyploid apomictic forms. Although the plants produce conspicuous flower heads with a copious amount of nectar and pollen, seeds are often produced asexually by diplospory [50]. The seeds disperse through wind or adhesion, often near to the parent plant [51].…”
Section: Methodsmentioning
confidence: 99%
“…Molecular marker studies lacked evidence for genetic exchange during this process, but more extensive studies on genetic consequences of possible recombination events have to be performed. Crossing studies revealed that diplospory and parthenogenesis inherit independently in T. officinale [51], whereas the precise inheritance of autonomous endosperm formation is yet unresolved. Diplospory showed dominant, monogenic inheritance, indicating genotypes Ddd , Dddd , and dd for tri- and tetraploid apomicts and diploid sexuals, respectively [44].…”
Section: Introductionmentioning
confidence: 99%